2012
DOI: 10.1186/1479-5876-10-197
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Cyfra21-1 and SCC-Ag serum titers predict survival in patients with stage II esophageal squamous cell carcinoma

Abstract: BackgroundThe purpose of this study is to evaluate the predictive significance of preoperative serum level of cytokeratin 19 fragments (Cyfra21-1) and squamous cell carcinoma antigen (SCC-Ag) after complete resection in patients with stage II esophageal squamous cell carcinoma (ESCC).MethodsBetween 1995 and 2006, a total of 379 patients in stage II ESCC who underwent complete resection were consecutively recruited. Statistical analyses were applied to test the associations between preoperative serum titers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 36 publications
(36 reference statements)
1
41
0
Order By: Relevance
“…In these cases of high morbidity, it was determined that the preoperative high-serum CYFRA 21-1 was a clear indicator of the occurrence of postoperative complications. CYFRA 21-1 is a cytoskeleton marker with a low-molecular weight (40 kDa), and is one of the serum tumor markers of squamous cell carcinomas (16)(17)(18). Recently, Vercauteren et al (24) reported that increased levels of serum CYFRA 21-1 were correlated with pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these cases of high morbidity, it was determined that the preoperative high-serum CYFRA 21-1 was a clear indicator of the occurrence of postoperative complications. CYFRA 21-1 is a cytoskeleton marker with a low-molecular weight (40 kDa), and is one of the serum tumor markers of squamous cell carcinomas (16)(17)(18). Recently, Vercauteren et al (24) reported that increased levels of serum CYFRA 21-1 were correlated with pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…These markers represent the patients' chronic systemic inflammation, immune status and nutritional condition. Furthermore, serum squamous cell carcinoma antigen (SCC-Ag) and cytokeratin 19 fragments (CYFRA 21-1) have been reported as good markers of ESCC progression (16)(17)(18).…”
Section: Evaluation Of Prognostic Markers For Patients With Curativelymentioning
confidence: 99%
See 1 more Smart Citation
“…High CYFRA21-1 level in patients is associated with poor prognosis. CEA is significantly associated with overall 5-year survival in ESCC 4951. Then, we compared our lncRNA biomarkers with the traditional tumor markers CYFRA21-1 and CEA.…”
Section: Resultsmentioning
confidence: 99%
“…6 CYFRA21-1 is a fragment of cytokeratin 19 and an important tumor marker. 19 Recently, Real-time polymerase chain reaction technology has been widely used to detect the micrometastases in peripheral blood (PB) by the expression of marker genes. 18 The preoperative serum level of Cyfra21-1 is an independent predictor which negatively affects the survival of patients with stage II ESCC.…”
Section: Introductionmentioning
confidence: 99%